Inheritance and development of traditional martial arts under the perspective of group dynamics: a case study of Ma’s Tongbei martial arts - Yang, Weilei; Huang, Yinwei (Frontiers in Psychology, 2025)
IntroductionIn the modern context, the inheritance and development of traditional martial arts face numerous challenges. This study focuses on Ma’s Tongbei martial arts and aims to explore its inheritance and development from the perspective of group dynamics. It will reveal the deep-seated principles of the traditional martial arts inheritance mechanism and provide references and inspirations for modern martial arts education.MethodsThis research mainly adopts the ethnographic research method to deeply analyze Ma’s Tongbei martial arts group and study its inheritance and development from the perspective of group dynamics.ResultsThe group structural characteristics of Ma’s Tongbei martial arts are analyzed, revealing the complex internal social relationships and norms within its unique social system, as well as the central position of the master-disciple relationship. It is found that group cohesion plays a crucial role in maintaining the stability of martial arts styles and promoting their development. It can inspire members to actively learn and inherit traditional skills and encourage innovation under the concept of “holistic integration and versatility in martial arts”, keeping Tongbei martial arts vibrant and adaptable to the needs of modern society.DiscussionThrough the analysis of the group dynamics of Ma’s Tongbei martial arts, this study provides important references and inspirations for modern martial arts education. Meanwhile, potential future research directions are pointed out, including the study of martial arts group dynamics in cross-cultural contexts and the exploration of interactions and group dynamics between different martial arts styles, aiming to provide theoretical support and practical guidance for the modern inheritance of traditional martial arts.